Study of nodulation and nitrogen fixation in two cowpea [Vigna unguiculata (L.) Walp.] cultivars inoculated with different strains of Bradyrhizobium sp. - Yu. V. Fotev; K. K. Sidorova; T. I. Novikova; V. P. Belousova (Вавиловский журнал генетики и селекции)
Cowpea (Vigna unguiculata L. Walp.) is a vegetable legume with promise for agricultural production in Russia. The impact of inoculation with three strains of Bradyrhizobium sp. from the All Russian Institute of Agricultural Microbiology (St. Petersburg) on nodulation and nitrogen fixation on two cowpea cultivars, Sibirskiy razmer and Yunnanskaya, has been explored All the strains used made both cultivars produce nitrogen fixing nodules. Differences between the varieties in the ability to form nodules and fix nitrogen following exposure to the different strains have been identified. High variation of the nodulation ability of both cultivars has been observed: at the beginning of flowering, the number of nodules per plant was 4–47 in Sibirskiy razmer and 17–117 in Yunnanskaya. Uninoculated vigna roots used as the control did not form nodules. At the beginning of flowering (48 days after inoculation) Sibirskiy razmer plants inoculated with strain 164 0503 (03) had the highest nodule weight per plant (0.79 g) and N2 fixation rates (5155.3 nmol С2H4/plant/h). The corresponding measures in Yunnanskaya were 1.41 g and 5255.5 nmol С2H4/plant/h following exposure to strain 162 0501 (01) and 4673.0 nmol С2H4/plant/h following exposure to strain (03). Analysis showed a correlation between nitrogen fixation rate and nodule weight (pcs./plant), r = 0.78 (p > 0.95). Data obtained suggest that effective symbioses are achieved between Sibirskiy razmer and strain 03 as well as between Yunnanskaya and strain 01.